2013
DOI: 10.1007/s11894-013-0322-8
|View full text |Cite
|
Sign up to set email alerts
|

Barrett’s Esophagus in 2012: Updates in Pathogenesis, Treatment, and Surveillance

Abstract: Barrett’s esophagus (BE) is the only established precursor lesion in the development of esophageal adenocarcinoma (EAC) and increases the risk of cancer by eleven fold. It is regarded as a complication of gastroesophageal reflux disease. There is ever increasing body of knowledge on the pathogenesis, diagnosis, treatment and surveillance of BE and its associated dysplasia. In this review, we summarize the latest advances in BE research and clinical practice in the past 2 years. It is critical to understand bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…Nodular lesions in dysplastic BE can be resected through either endoscopic mucosal resection or endoscopic submucosal dissection. 75 Pech and colleagues 76 compared endoscopic resection to esophagectomy in a multicenter retrospective cohort study and found complete remission in 98.7% of subjects treated with endoscopic resection. Few subjects undergoing endoscopic resection had complications, whereas 32% had major complications after esophagectomy.…”
Section: Esophageal Adenocarcinomamentioning
confidence: 99%
“…Nodular lesions in dysplastic BE can be resected through either endoscopic mucosal resection or endoscopic submucosal dissection. 75 Pech and colleagues 76 compared endoscopic resection to esophagectomy in a multicenter retrospective cohort study and found complete remission in 98.7% of subjects treated with endoscopic resection. Few subjects undergoing endoscopic resection had complications, whereas 32% had major complications after esophagectomy.…”
Section: Esophageal Adenocarcinomamentioning
confidence: 99%
“…[6] Epidemiological studies have revealed that adenocarcinomas occur from BE through multistep morphological changes, such as low-grade to high-grade dysplasia. [6,7] BE and EGJ adenocarcinoma/ EAC share poly-genetic/epigenetic alterations. [8] BE can be described as mucosal replacement of normal squamous epithelium with metaplastic columnar mucosa, known as specialized columnar metaplasia, in response to chronic gastroesophageal refl ux disease (GERD).…”
Section: Introductionmentioning
confidence: 99%
“…It comprises approximately 0.36%-2.8% of all esophageal malignancies. [1,2] According to a literature search using PubMed, most reported cases were smaller than 17 cm in length, while a tumor occupying the entire esophagus was quite less frequently seen. [3] Right aortic arch (RAA) is an intrathoracic great vessel anomaly that has been reported to be present in 0.04%-0.1% of autopsy cases.…”
Section: Introductionmentioning
confidence: 99%